2018
DOI: 10.1002/ece3.4653
|View full text |Cite
|
Sign up to set email alerts
|

Environmental DNA analysis as a non‐invasive quantitative tool for reproductive migration of a threatened endemic fish in rivers

Abstract: Quantitative information regarding reproduction is essential for conserving endangered animals; however, some conventional quantitative methods can be damaging to the target population and their habitats. In the present study, the reproductive migration of a threatened endemic fish, three‐lips (Opsariichthys uncirostris uncirostris), was non‐invasively monitored by quantitative PCR of species‐specific environmental DNA (eDNA), the usefulness of which has been not sufficiently explored. Water sampling and from‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
40
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(43 citation statements)
references
References 43 publications
3
40
0
Order By: Relevance
“…In addition, eDNA concentrations can reflect the relative abundance of target species in aquatic environments (Eichmiller et al, ; Mizumoto, Urabe, Kanbe, Fukushima, & Araki, ; Takahara, Minamoto, Yamanaka, Doi, & Kawabata, ; Yates, Fraser, & Derry, ), even in streams (Doi et al, ; Lacoursière‐Roussel, Côté, Leclerc, & Bernatchez, ; Pilliod, Goldberg, Arkle, Waits, & Richardson, ; Tillotson et al, ). This technique is also useful for detecting the seasonal habitat changes of migratory fishes (Laramie, Pilliod, & Goldberg, ; Maruyama, Sugatani, Watanabe, Yamanaka, & Imamura, ; Yamanaka & Minamoto, ).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, eDNA concentrations can reflect the relative abundance of target species in aquatic environments (Eichmiller et al, ; Mizumoto, Urabe, Kanbe, Fukushima, & Araki, ; Takahara, Minamoto, Yamanaka, Doi, & Kawabata, ; Yates, Fraser, & Derry, ), even in streams (Doi et al, ; Lacoursière‐Roussel, Côté, Leclerc, & Bernatchez, ; Pilliod, Goldberg, Arkle, Waits, & Richardson, ; Tillotson et al, ). This technique is also useful for detecting the seasonal habitat changes of migratory fishes (Laramie, Pilliod, & Goldberg, ; Maruyama, Sugatani, Watanabe, Yamanaka, & Imamura, ; Yamanaka & Minamoto, ).…”
Section: Introductionmentioning
confidence: 99%
“…Tank experiments in our previous study (Mizumoto et al, 2018) revealed a high sensitivity of the Sakhalin taimen eDNA detection system and its potential for biomass estimation in flowing waters. In general, however, the detectability of eDNA from aquatic organisms is affected by both biotic and abiotic factors such as the range from the target species, sizes and density of them, water temperature, pH, water current, flow volume and so on (e.g., Barnes et al, 2014;Song et al, 2017; Maruyama et al, 2018;Kasai et al, 2020). Therefore, actual detectability of Sakhalin taimen's eDNA in the natural river systems would rather be limited, and we are almost certain that we missed eDNA detections from some river systems, especially from large rivers or areas with low density of Sakhalin taimen.…”
Section: Discussionmentioning
confidence: 99%
“…These techniques have many advantages for detecting target species in the field, such as objectivity, high detectability, and reduced sampling effort. They have been shown to be especially useful for monitoring endangered species that are otherwise difficult to capture or observe (Fukumoto et al, 2015;Laramie et al, 2015;Pfleger et al, 2016;Carlsson et al, 2017;Maruyama et al, 2018;Atkinson et al, 2019;Iwai et al, 2019). However, the previous studies tended to apply the eDNA techniques to specific freshwater/saltwater systems or to relatively small geographical regions.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the use of environmental DNA (eDNA), which is the trace amounts of DNA discharged by organisms via excretion of urine, feces, body cells, eggs, etc., enables the non-invasive detection of species and their approximate relative quantification 6 9 . Whole fish communities can be characterized from eDNA using high throughput sequencing or specific amplicons—a process known as eDNA metabarcoding 10 14 .…”
Section: Introductionmentioning
confidence: 99%